Relationship between language learning strategy use and language proficiency among students in Malaysian independent Chinese secondary schools - Lye, Che Yee (2012)
Literature on language learning strategy use indicates that high and low proficiency language learners use strategies differently and that these differences are related to differences in their language proficiency. However, to date, no study has been done in the Malaysian Independent Chinese Secondary Schools (MICSS) to examine the relationship between language learning strategy use and language proficiency. The current study is timely and relevant as it examined the language learning strategies employed by high and low language proficiency students, as well as the relationship between language learning strategy use and language proficiency. The participants in this study were 517 Senior One MICSS students selected based on cluster sampling. The Strategy Inventory for Language Learning (SILL) questionnaire developed by Oxford (1990) was used to elicit data on language learning strategies. The SILL questionnaire consisted of six groups: Memory,Cognitive, Compensation, Metacognitive, Affective and Social. The SILL questionnaire was translated into Chinese language using the parallel translation method so that low English language proficiency students understand the content of the questionnaire. Language proficiency was determined using the Junior level Unified Examination Certificate (UEC) English language test. In order to find the answers for the differences of strategy group and specific strategies employed by high and low language proficiency students, the mean scores of the six groups of strategies and the mean scores of the 50 specific strategies were first examined and then compared between high and low language proficiency groups by using Multivariate Analysis of Variance (MANOVA). Furthermore, in order to examine the relationship between language learning strategy use and language proficiency of high and low language proficiency students, the Structural Equation Modelling (SEM) method was used. A two-step approach proposed by Anderson and Gerbing (1998) was used to construct the measurement and structural models. The structural models were also compared using the multi-group analysis. The results of the study show that high language proficiency student employed the six strategy groups significantly more frequent than the low language proficiency students. The study also found that high language proficiency students employed a wide range of strategies in their learning of English. While the rank order of the strategy group use did not differ much between the two groups, high language proficiency students often used the specific strategies listed in the SILL questionnaire significantly more frequent than low language proficiency students. The SEM results showed that while language learning strategies consist of six groups, the MICSS students combined four groups of strategies when learning English. The combination of Memory, Cognitive, Metacognitive and Social strategy use contributed significantly highly to the Grammar performance of low language proficiency students. However, the use of Compensation strategies brought significant moderate adverse effects on the Grammar performance of low language proficiency students. SEM results also showed that the contribution of the combination of Memory,Cognitive, Metacognitive and Social strategy use to Grammar performance of low language proficiency students was significantly higher than high language proficiency students.